1966
DOI: 10.1002/zaac.19663440502
|View full text |Cite
|
Sign up to set email alerts
|

Verbindungen im System BCSi bzw. BSi

Abstract: Im elektrischen Lichtbogen wurden zwei neue Verbindungen hergestellt. Der säureunlösliche Anteil erwies sich röntgenographisch als dem Borcarbid sehr ähnlich mit a0 = 5,65 Å und c0 = 12,35 Å. In Verbindung mit der chemischen Analyse kann auf eine Substitutionsverbindung B12(C, Si, B)3 geschlossen werden. Die Mikrohärte wurde mit 2,450 kg · mm−2, die pyknometrische Dichte mit 2,52 g · cm−3 gemessen. Eine ähnliche Verbindung mit den hexagonalen Gitterkonstanten a0 = 5,62 Å und c0 = 12,34 Å wurde neben SiC aus Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…Our bulk calculations give the lattice constants of a = 3.067Å, c = 3.515Å, which are in good agreement with experimental and other theoretical results [5,13]. We used this bulk geometry as the initial geometry for the surface optimizations.…”
supporting
confidence: 83%
“…Our bulk calculations give the lattice constants of a = 3.067Å, c = 3.515Å, which are in good agreement with experimental and other theoretical results [5,13]. We used this bulk geometry as the initial geometry for the surface optimizations.…”
supporting
confidence: 83%
“…Shaffer [32] reported that well formed SiC crystals have a boron solubility limit of 0.1-0.15 wt.% and less perfectly formed crystal show boron concentrations above 0.2 wt.%. The maximum solubility of Si in B 4 C at 2323 K was found to be 2.5 at.% [34]. This was later confirmed by Werheit et al [35] using optical absorption spectrum.…”
Section: The B-c-si Ternary Systemmentioning
confidence: 71%
“…The significant enlargement observed for the c axis is consistent with the occupation of the 6 c site by Li + . In the case of the incorporation of Al or Si atoms into the framework of α‐rhombohedral boron the expansion of the unit cell is mainly due to an enlargement of the a axis, thus indicating a different type of substitution …”
Section: Resultsmentioning
confidence: 99%
“…One way to shed light on the bonding situation in boron carbide is the incorporation of additional elements, aiming at a situation with an electron‐precise structure and a large bandgap. About 50 years ago there were reports on boron carbide with additional aluminum or silicon atoms, resulting in rhombohedral structures with slightly enlarged lattice parameters, but no details on the structures were given. Furthermore, the color of crystals was described as black.…”
Section: Introductionmentioning
confidence: 99%